The effects of a disulphonic stilbene on chloride and bicarbonate transport in the turtle bladder. - Brodsky, W A (1979)
1. In turtle bladders bathed by Na-free media containing Cl and HCO3, the mucosa is electropositive to the serosa. Serosally applied 4-acetamido-4'-isothiocyano-2,2'-disulphonic stilbene (SITS) reduces the p.d. and Isc by 100%, and reduces the rate of net Cl reabsorption in some bladders but not in others. 2. In the absence of exogenous HCO2 (Cl present), SITS reduces the p.d. and Isc by 100%, and reduces the rate of mucosal acidification by 80%; net Cl reabsorption is not detectable under these HCO3-free bathing conditions. 3. In the absence of exogenous Cl (HCO3, present), the mucosa is also electropositive to the serosa and serosally applied SITS reverses the orientation of the p.d. and Isc so that the mucosa becomes electronegative to the serosa. 4. This constitutes sufficient evidence for the active, electrogenic secretion of an anion, probably HCO3. These data are explained by an analogue of discrete, electrogenic pumps and paths for the reabsorption of Na, Cl, and HCO3, and the secretion of HCO3.